Erratum on the article ‘Planning of tunneling projects using computer simulation and fuzzy decision making’ (DOI:10.3846/13923730.2013.793608) - Abdallah, Moatassem; Marzouk, Mohamed (Journal of Civil Engineering and Management, 2013)
Erratum on the article ‘Planning of Tunneling Projects using Computer Simulation and Fuzzy Decision Making (doi: 10.3846/13923730.2013.793608). Journal of Civil Engineering and management, 19(5), p. 773.